Anthocyanin pigmentation as a quantitative visual marker for arbuscular mycorrhizal fungal colonization of Medicago truncatula roots - Kumar, Anil (The New phytologist, 2022)
© 2022 The Authors. New Phytologist © 2022 New Phytologist Foundation.